Containment, activism and state racism: the Sheku Bayoh justice campaign. Issue 2 (4th March 2022) - Akhtar, Smina
ABSTRACT: This article develops a framework to think sociologically about the containment of activism in contexts of state racism. It argues that normal everyday practices of the police and judicial system have mechanisms which contain challenges to their authority. It shows how state racism is embedded within the criminalisation of black people and enacted through policing. The analysis focuses on Scotland's first black death in police custody and the campaign formed by his family to establish the circumstances of the death. Sheku Bayoh died shortly after being arrested and restrained by up to nine police officers in Kirkcaldy, a small town on the east coast of Scotland, in May 2015. I pay attention to the role played by racism in the media's framing of Sheku's death, common in explaining deaths of black people at the hands of the police.